Model Pembelajaran Magang dalam MBKM Prodi PG-PAUD Universitas Trilogi - Roostrianawahti Soekmono; Mia Rachmawaty; Duana Fera Risina (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
This study aims to describe the results of the MBKM implementation survey in the PG-PAUD Study Program, Trilogy University. In particular, this study aims to describe the implementation of the internship program carried out in the PG-PAUD Study Program, Trilogy University. Based on the results of a survey conducted in the PG-PAUD Study Program, the highest percentage was in the implementation of the internship/work practice program at 54%. The internship model at MBKM that has been developed in the PG-PAUD study program is Field observation practice or internship 1 in semester 3 (s credits), teaching practice or internship 2 in semester 5 (2 credits), and advanced teaching practice or internship 3 in semester 7 (4 credits). This internship program is in the form of an internship for 6 months and 8 days and is greater than the minimum target of an internship, which is 5 months. In addition, the internship method is carried out in stages and can be done offline or online. During the COVID-19 pandemic, the internship program will continue to be carried out online. In addition, students are also free to choose public and private PAUD schools and PAUD schools that have certain characteristics.Keywords: Learning model; Internship; Merdeka Learning Merdeka Campus (MBKM) Abstrak Penelitian ini bertujuan untuk mendeskripsikan hasil survey pelaksanaan MBKM di Program Studi PG-PAUD Universitas Trilogi. Secara khusus penelitian ini bertujuan untuk mendeskripsikan pelaksanaan program magang yang dilaksanakan di Program Studi PG-PAUD Universitas Trilogi. Berdasarkan hasil survey yang dilakukan di Program Studi PG-PAUD hasil prosentase tertinggi pada pelaksanaan program magang/praktik kerja sebesar 54%. Model magang pada MBKM yang sudah dikembangkan pada program studi PG-PAUD yaitu Praktek observasi lapangan atau magang 1 pada semester 3 (s sks), Praktik mengajar atau magang 2 pada semester 5 (2 sks) dan praktik mengajar lanjutan atau magang 3 pada semester 7 (4 sks). Program pelaksanaan magang ini berupa magang selama 6 bulan 8 hari dan lebih besar dari target minimal magang yaitu 5 bulan. Selain itu metode magang dilakukan secara bertahap dan bisa dilakukan secara luring maupun daring. Selama pandemic covid 19 program magang tetap dilaksanakan secara daring. Selain itu mahasiswa juga dibebaskan untuk memilih sekolah PAUD Negeri maupun Swasta dan sekolah PAUD yang memiliki ciri khas tertentu.Keywords: Model pembelajaran; Magang; Merdeka Belajar Kampus Merdeka (MBKM)